К нам едет Пересвет: отчет за нулевые: [эссе] / Захар Прилепин - Прилепин Захар Николаевич (Астрель, 2012)
Экземпляры: аб. (2013) / Инвентарный номер: 49638 / Цена: / Сис.шифр: 84.2Рос6 / Авт.знак: П 76 / ББК: 84(2Рос=Рус)6